Momentum transfer to Newtonian and non-Newtonian fluids flowing through packed and fluidized beds - Mishra P.; Singh D.; Mishra I.M. (My University, 2025)
This paper deals with the flow behaviour of Newtonian and non-Newtonian fluids flowing through packed and expanded beds. With the help of tube-bundle theory a generalized average shear-stress-shear-rate relationship is derived and found to predict the flow behaviour of power law as well as non-power law fluids. Polyvinyl alcohol solutions in water, a representative of power law fluids, and grease in kerosene, a representative of nonpower law fluids, are studied. The present investigation covers the range of Reynolds number from 10-3 to 103. An expression for average shear-stress at minimum fluidization velocity is derived and found to agree with that of our experiment. The generalized frictional Reynolds number is defined and a design chart is also presented for the evaluation of fluidizing velocities. © 1975.